2017
DOI: 10.1097/sap.0000000000001132
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of 4 Analgesic Regimens for Acute Postoperative Pain Control in Breast Augmentation Patients

Abstract: When given options for pain control in breast augmentation, intraoperative ketorolac should be considered, because its inclusion was significant in decreasing use of narcotics and pain upon discharge. Addition of other costly drugs such as liposomal bupivacaine may not provide additional benefit in the immediate postoperative setting for procedures with a short recovery period such as breast augmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Other clinical factors may affect analgesic efficacy as well, such as anatomical site, tissue vascularity, the variability of surgical procedures, and the coadministration of systemic analgesics. In fact, several studies of local infiltration in breast surgery, 31 urological laparoscopic surgery, 32 and total knee replacement, 33 reported that liposomal bupivacaine was not superior to conventional bupivacaine in analgesic efficacy.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%
“…Other clinical factors may affect analgesic efficacy as well, such as anatomical site, tissue vascularity, the variability of surgical procedures, and the coadministration of systemic analgesics. In fact, several studies of local infiltration in breast surgery, 31 urological laparoscopic surgery, 32 and total knee replacement, 33 reported that liposomal bupivacaine was not superior to conventional bupivacaine in analgesic efficacy.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%
“…IV administration of ketorolac (30 or 60 mg), has decreased the postoperative pain severity and subsequent need for opioid analgesics in the recovery period. 24,25 It is beyond doubt that IV lignocaine infusion is an appealing option for perioperative pain management as suggested by our and other studies. Lignocaine infusion is easy to administer and is inexpensive.…”
Section: Discussionmentioning
confidence: 72%
“…Various techniques, such as intravenous analgesics, thoracic epidural analgesia, thoracic paravertebral block, intercostal blockade, and PECS blocks, may be used for postoperative pain treatment following breast augmentation surgery. 6 , 7 , 8 , 9 , 14 PECS block type-1 is commonly used under US guidance because it is a superfascial block, easy to administer, and has relatively low complication rates. The mechanism of action of PECS block type-1 is related to the neural anatomy of the chest wall, which contains three groups of nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have addressed postoperative analgesia management following breast augmentation. 6 , 7 , 8 , 9 A number of studies have also investigated the efficacy of PECS block for postoperative pain treatment following different types of breast surgery, such as carcinoma, reconstructive, and cosmetic surgeries. 10 , 11 , 12 , 13 , 14 However, to the best of our knowledge, there is no study that evaluates the timing (preoperatively or postoperatively) of the PECS block in the literature.…”
Section: Introductionmentioning
confidence: 99%